Biological Form is Sufficient to Create a Biological Motion Sex Aftereffect. (October 2016) - Hiris, Eric; Mirenzi, Aaron; Janis, Katie
In a series of five experiments we sought to determine what causes the biological motion sex aftereffect—adaptation of a general representation of the stimulus sex, adaptation to the motion in the stimulus, or adaptation to the form in the stimulus. The experiments showed that (a) adaptation to gendered faces and gendered full body images did not create a biological motion sex aftereffect; (b) adaptation to moving partial biological motion displays containing the most important motion cues for sex discrimination (shoulders and hips or shoulders, hips, and feet) did not create a biological motion sex aftereffect; and (c) adaptation to a static frame or shapes derived from a static frame did create a biological motion sex aftereffect. These results suggest that form information is sufficient to create a biological motion sex aftereffect and suggests that biological motion sex aftereffects may be a result of lower level rather than higher level adaptation in the visual system.